2012
DOI: 10.1093/jpids/pis042
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Mold Infections in Pediatric Cancer Patients Reflect Heterogeneity in Etiology, Presentation, and Outcome: A 10-Year, Single-Institution, Retrospective Study

Abstract: Although Aspergillus spp. was the most common mold in our pediatric cancer population, the epidemiology of the IMIs was diverse. Adults and children share similar risk factors for and epidemiology of IMIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 56 publications
3
52
2
6
Order By: Relevance
“…Pediatric Invasive Mold Infections differences in global treatment success, progression-free survival, or mortality when comparing patients with different IMI types, but small numbers of patients with mucormycosis or other IMIs limit conclusions regarding outcome by subtype. The 12-week mortality rate of 30% in our cohort is similar to the 31% 12-week mortality rates from recent single-center cohort studies of IMIs in children with cancer or receiving HSCT [5,24]. The long-term mortality rate reported for one of these studies was much higher at 73%, and prior pediatric cohort studies, primarily focusing on IA, have reported similarly poor long-term mortality rates, ranging from 50% to 88% [3-5, 7, 25, 26].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Pediatric Invasive Mold Infections differences in global treatment success, progression-free survival, or mortality when comparing patients with different IMI types, but small numbers of patients with mucormycosis or other IMIs limit conclusions regarding outcome by subtype. The 12-week mortality rate of 30% in our cohort is similar to the 31% 12-week mortality rates from recent single-center cohort studies of IMIs in children with cancer or receiving HSCT [5,24]. The long-term mortality rate reported for one of these studies was much higher at 73%, and prior pediatric cohort studies, primarily focusing on IA, have reported similarly poor long-term mortality rates, ranging from 50% to 88% [3-5, 7, 25, 26].…”
Section: Discussionsupporting
confidence: 85%
“…Although data for combination antifungal therapy in children with IMIs are sparse, it is frequently used in practice, as evidenced by our study and by other recent pediatric cohort studies that have reported rates of combination therapy ranging from 32% to 91% [3][4][5]. We found that primary combination therapy was more likely to be used in patients who had received antimold agents before diagnosis.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Lomentospora prolificans was the most commonly encountered non‐ Aspergillus mold in our study, and although reported in previous predominantly adult Australian studies, it rarely features in pediatric series . There is also a striking paucity of mucormycosis, which is in contrast to other international paediatric and local adult studies. Variations in the prevalence and epidemiology of non‐ Aspergillus mold infections may reflect selective antifungal pressure through antifungal prophylaxis strategies and local environmental influences, such as agricultural antifungal use and construction works and highlights the importance of ongoing evaluations of local IFI epidemiology and outcomes in specific diagnostic and HSCT cohorts to optimize prevention and treatment strategies to minimize IFI morbidity and mortality.…”
Section: Discussioncontrasting
confidence: 54%